DEVELOPMENT AND EVALUATION OF TERMINALIA CHEBULA HERBAL MOUTHWASH - DR. MANISHA S. NANGUDE; MADHURA G BHOIR; DIVYA R. BHAWARI; SANJANA S. BHERE; BHUVANESHWARI S. BHOIR; GAURI G. BHAMRE; SUVIDHA S. KABADI (The Bioscan, 2026)
This study investigates the antibacterial potential of Terminalia chebula against Streptococcus mutans, a primary cause of dental caries. An herbal mouthwash was formulated using aqueous extracts of T. chebula, honey, and polyethylene glycol. Phytochemical screening revealed the presence of bioactive compounds like tannins, flavonoids, and saponins. GC-MS analysis identified a complex chemical profile dominated by antioxidant-rich compounds, including siloxanes, phosphites, and natural esters. The formulation exhibited significant antibacterial activity, with Formulation F3 showing 98.88% microbial reduction. The mouthwash demonstrated physical stability over 30 days, maintaining consistent color, odor, taste, and pH.